2022
DOI: 10.3390/ijms232012116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Subthalamic Stimulation and Electrode Implantation in the Striatal Microenvironment in a Parkinson’s Disease Rat Model

Abstract: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is considered the gold-standard treatment for PD; however, underlying therapeutic mechanisms need to be comprehensively elucidated, especially in relation to glial cells. We aimed to understand the effects of STN-microlesions and STN-DBS on striatal glial cells, inflammation, and extracellular glutamate/GABAergic concentration in a 6-hydroxydopamine (6-OHDA)-induced PD rat model. Rats with unilateral striatal 6-OHDA and electrodes implanted in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 78 publications
2
2
0
Order By: Relevance
“…In our study, the expression of IL-6-positive cells in the SNpc and VTA was reduced after the application of DBS-STN in the 6-OHDA model of PD. These results are similar to the last study of Pinheiro Campos [34]. They found that 6-OHDA-lesioned rats exhibited increased immunoreactivity of Iba-1 and increased expression of CX3CL1, TNF-α, IL-1β, IL-6, and IFN-γ.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, the expression of IL-6-positive cells in the SNpc and VTA was reduced after the application of DBS-STN in the 6-OHDA model of PD. These results are similar to the last study of Pinheiro Campos [34]. They found that 6-OHDA-lesioned rats exhibited increased immunoreactivity of Iba-1 and increased expression of CX3CL1, TNF-α, IL-1β, IL-6, and IFN-γ.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study performed by our research team showed also that the electrical or pharmacological activation of the VTA influences peripheral blood immunity, feeding behavior, and neuronal activation in the hypothalamus [31,32]. Since pro-inflammatory activity is hypothesized to be already present in the prodromal stages of PD [33] and DBS-STN is considered to be a potential anti-inflammatory method [30,34], explaining the mechanism of DBS-STN seems important for its use in PD patients. To study the effects of DBS-STN applied in partially nigral-depleted Wistar male rats on neuronal activation and neuroinflammation, we measured IL-6 and cFos expression in the dopaminergic structures of the nigriostriatal (substantia nigra pars compacta, SNpc) and mesolimbic (VTA) systems.…”
Section: Introductionmentioning
confidence: 91%
“…The control of vesicle transport by Rab8a may facilitate the formation of different membrane protrusions, while VAMP2 and Syntaxin16, components of the SNARE complex, are critical proteins in vesicle docking. Our results, combined with previous studies [65,66], suggest that Rab8a-mediated enhanced transport of vesicles from the trans-Golgi network (TGN) to the plasma membrane may underpin the molecular basis for astrocyte release of bioactive molecules involved in the onset and maintenance of NPP. Enhanced vesicular transport in LPS-activated astrocyte models likely represents a crucial mechanism for the secretion of bioactive molecules by activated astrocytes, with activated pathways for cytokine synthesis and secretion contributing to disease progression.…”
supporting
confidence: 73%
“…PD pathophysiology is associated with misfolding of α-synucleina protein whose aggregation leads to the formation of inclusions termed Lewy bodiesand the progressive loss of dopaminergic neurons in the substantia nigra (a component of the basal ganglia). The involvement of EAAT2 was mostly demonstrated in experimental models of PD, highlighting the strong association between reactive astrocytes and EAAT2 loss in the striatum. Interestingly, Wnt1 promoted increased EAAT2 expression in astrocytes which induced protective effects on dopaminergic neurons . Another study reported that exercise intervention in 6-hydroxydopamine-induced PD rats significantly improved the motor dysfunction of PD model rats, increased the ability of striatal glutamate reuptake significantly, and upregulated the expression levels of EAAT2 protein .…”
Section: Eaat2 In Brain Disordersmentioning
confidence: 99%